A short survey of bicyclic diamines-syntheses and properties of N,N′-bridged-1,10-diazabicyclooctadeca-5,14-diynes - Hirschheydt, Thomas von; Wolfart, Volker; Gleiter, Rolf; Irngartinger, Hermann; Oeser, Thomas; Rominger, Frank; Eisenträger, Frank (Perkin, 2000)
The conformations and properties of 1,(k + 2)-diazabicyclo[k.l.m]alkanes are reviewed briefly. In these species the alkane chains allow inside protonation but no metal complexation. Inside metal complexation is made possible if the alkane chains incorporate alkyne units. The preparation and structures of bridged 1,10-diazacyclooctadeca-5,14-diynes are reported. As bridges we use simple alkyl chains from (CH2)2 to (CH2)10, di- and triethyleneglycol, but-2-yne, hex-3-yne, and oct-4-yne chains. The resulting bicyclic systems, 34-47, adopt in the solid state either the in/in or the out/out conformations. By means of dynamic NMR spectroscopy a homeomorphic isomerism in 34 was uncovered. A second dynamic process, a “wagging” motion of the alkyne bridges, could be studied in case of 35. The molecular dimensions in the solid state reveal N⋯N distances between 3.16 Å and 6.52 Å. The intramolecular distances between the triple bonds vary between 4.25 Å and 7.31 Å.
Gesehen am 04.11.2020